Neuroticism, Social Avoidance and Distress, and Problematic Internet Use Among College Students: A Longitudinal Mediation Model. - Kong, Anran; Zhou, Haotian (International Journal of Mental Health & Addiction, 2026)
This study aims to explore the longitudinal relationships between neuroticism, social avoidance and distress, and Problematic Internet use (PIU). We utilized scales for these variables to conduct three follow-up surveys over 1 year with 397 college students. The findings reveal that social avoidance and distress mediate the relationship between neuroticism and Problematic Internet use (PIU) over time. Additionally, Problematic Internet use (PIU) also serves as a longitudinal mediator between neuroticism and social avoidance and distress. The study concludes that there is a cyclical causality among social avoidance, distress, and Problematic Internet use (PIU), with neuroticism predicting both. Enhancing interventions for social avoidance and distress can effectively reduce the risk of Problematic Internet use (PIU) among college students, while regulating internet use can improve their social skills and overall well-being.